Legal Reform on Corporate Responsibility in The Disruption Era (Study of Legal Issuese-Commerce) - Muhammad Husni Fahruddin (International Peneliti Ekonomi, Sosial dan Teknologi, 2023)
The speed of technological development has changed the way humans live dramatically, the world is changing very quickly into the